Analisis Strategis IS/IT sebagai Dasar Perumusan Strategi Teknologi Informasi Organisasi - Nursinta, Nursinta; Listyo Probowo, Sugeng (Indo-MathEdu Intellectuals Journal, 2026)
This study examines the role of strategic IS/IT analysis as the foundation for formulating effective and sustainable information technology strategies. Using a systematic literature review of publications from 2023–2025, the study analyzes strategic frameworks, implementation challenges, and best practices for integrating IS/IT with business objectives. Data analysis is conducted thematically through coding, categorization, synthesis, and interpretation to identify the implications of findings. Research quality is maintained through source triangulation, data transparency, structured review protocols, and systematic documentation. The findings indicate that organizations aligning IS/IT strategy with business strategy achieve 20–30% improvements in operational efficiency, competitive advantage, and better adaptation to market changes. The main frameworks identified include the Strategic Alignment Model (SAM), SWOT Analysis, Porter’s Five Forces, and Value Chain Analysis. Implementation challenges include traditional perceptions of IT as a utility, system complexity, skill gaps, and organizational resistance. Recommended best practices include cross-functional collaboration, data-driven decision-making, adoption of agile operating models, and proactive partnerships between CIOs and CEOs. This study provides practical recommendations for practitioners and academics in designing IS/IT strategies oriented toward business value in the digital era